IMPLEMENTASI SUPERVISI AKADEMIK DALAM PENGEMBANGAN PROFESI GURU OLEH KEPALA SEKOLAH MENENGAH ATAS (SMA) BLOKAGUNG TEGALSARI BANYUWANGI - M Imam Khaudli; Elfa Naily Sari (Institut Agama Islam Darussalam Blokagung, 2022)
Academic supervision is a series of activities to help teachers develop their ability to manage the learning process to achieve learning objectives. The principal is one of the keys to the success of a quality educational institution in both process and output, therefore the principal as a supervisor is expected to motivate, foster, and develop teacher competence for the development of the teaching profession. The quality of education that runs effectively and efficiently is related to the principal's leadership with how the principal can influence teachers and school employees to achieve the vision, mission, and school goals that have been previously planned in developing the teaching profession at SMA Blokagung Tegalsari Banyuwangi. This study reveals the implementation of academic supervision in the development of the teaching profession at SMA Blokagung Tegalsari Banyuwangi, with the research focus: 1) planning for academic supervision carried out by the head of SMA Blokagung Tegalsari Banyuwangi 2) implementation of academic supervision by the head of SMA Blokagung Tegalsari Banyuwangi 3) the impact of academic supervision in professional development by the principal of SMA Blokagung Tegalsari Banyuwangi. This study uses a qualitative approach. The methods used in data collection include 1) interviews/ interviews 2) observation 3) documentation. These three methods are used to obtain research findings, these are analyzed by data reduction, data presentation, and data verification and drawing conclusions. The triangulation used includes several components: 1) Triangulation with theory; 2) Triangulation by method; 3) Triangulation with investigators. The results showed that: 1) Planning for the academic supervision of the principal at SMA Blokagung Tegalsari Banyuwangi based on increasing competence and the teaching profession is an activity that is carried out every semester change by involving all waka and senior teachers. 2) the implementation of individual academic supervision includes class visits, observations, individual meetings, and self-assessment. Followed up with group techniques include holding meetings, holding group discussions, and conducting upgrading. 3) academic supervision has a real impact on the professional development of teachers at SMA Blokagung Tegalsari Banyuwangi so that teachers can find out shortcomings when teaching and teachers know things that need to be addressed and improve the quality of learning in the classroom